LITHOFACIES INTERPRETATION OF CORE SAMPLES IN THE TANJUNG PASIR BEACH, TELUK NAGA, TANGERANG, BANTEN - Suwondo, Suwondo; Azizah, Sundus Ghaida Noor; Krisyunianto, Andi; Budiono, Agus (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2025)
This research was conducted at Tanjung Pasir Beach, Teluk Naga Sub-district, Tangerang Regency, Banten. The objective of this research was to analyze the sedimentary structures, describe lithology, and determine facies in a depositional environment. This facies interpretation can be as a reservoir analogue for subsurface interpretation in the Northwest Java Basin. The research data used include surface sand samples and core samples from Tanjung Pasir Beach. The facies interpretation shows that core at location 1 is dominated by carbonaceous shale with parallel lamination structures, indicating sedimentary of lagoon environment. In contrast, core at location 2 is predominantly composed of medium- to coarse-grained sandstone facies, representing a shoreface environment.